Implementation of Restorative Justice in Settlement of Criminal Actions in the Criminal System in Indonesia - Syarifuddin, Syarifuddin; Purba, Indra Gunawan; Putra, Panca Sarjana (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
Resolving several years of criminal offenses using a